EVALUASI EFEKTIVITAS PENGGUNAAN MEDIA PEMBELAJARAN INTERAKTIF DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA SEKOLAH DASAR - Baharuddin, Baharuddin; Nujud, Yasub Atsyir; Pasaribu, Muhammad Syafaruddin; Rafa, Juana (Universitas Muhammadiyah Tapanuli Selatan, 2024)
This research aims to provide a description of the evaluation of the use of learning media carried out by teachers as an effort to increase student learning motivation in elementary schools. In detail, this research aims to find out (a.) the definition related to learning media and also the learning motivation given by teachers to their students. (b.) The effectiveness of using learning media at school as a motivation for student learning. In this research, the author used a descriptive qualitative research method with techniques for collecting data using literature studies sourced from interviews, several books, journals, documents, and also valid websites. The results of this research have the aim that to become a teacher at school, of course you must also have the ability to provide learning motivation which is used as encouragement for students in the learning process.